Selected Topics on Infant Feeding - Jaber AL-Zwaini, Isam; Hadi AL-Musawi, Haider (IntechOpen, 2022)
The growth and development of infants during the first two years of life are greatly influenced by nutrition. Meeting basic nutritional requirements is vital for proper and optimal growth and development, both physically and mentally. Many factors have influenced the rate of breastfeeding and the proper timing of complementary feed introduction. Some of these factors include poverty, world wars, the influx of women into the workforce, and the development of commercial infant formula. This book presents a comprehensive overview of infant and young child feeding. Chapters address breastfeeding programs, infant feeding in developing countries, breastfeeding during the COVID-19 pandemic, and the safety and physiological effects of the formula.